Institutional Development in the .Nile Equatorial Lakes Sub·basin Learning from the Experience ofthe Kagera Basin Organisation - Mbaziira, Rashid; Senfuma, Nsubuga; McDonnell, Rachael (IWMI, 2005)
The interaction between natural resources development and the deployment of social resources is vital to understand when designing management institutions. As we look to the future management and development of the Nile River Basin Water Resources through the Nile Basin Initiative (NBI), it is useful to analyse and draw lessons from the institutional design and performance of the now defunct Kagera Basin Organisation (KBO). Established with a wide mandate that in a progressive institution would have presented increased opportunities for trade-offs among the participants, the KBO lacked the adaptive capacity to survive the historical, political and cultural dynamics between the riparians. Its experience provides invaluable institutional development lessons regarding political stability; commitment; and financial resources mobilisation, but the key lesson learnt is that a sustainability level of social resources will be required to identify, define and deploy the appropriate development, reform and adaptation mechanisms to transform the NBI into a lasting regime of cooperation.
Keywords: Regime formation; Institutional development; Regional cooperation; River basin organisations; Kagera Basin Organisation; Nile Basin Initiative